Influência dos determinantes ambientais no desenvolvimento motor de crianças das creches públicas de Aracaju-SE - Chile, Dayane Mello Pattis (2013)
The infant motor development is the individual s ability to perform increasingly complex functions and is associated with age. The development is due to the requirement of the task, the biology of the individual and the interaction with the environment in which it entered, and this interaction acts decisively and may aggravate or mitigate the impact of development on biological risk. Motor delays at this stage of development cause damage that may extend into adulthood. The present study aims at analyzing the influence of environmental determinants on motor development of children from public daycare centers in Aracaju / SE, whose instrument of data collection was the Alberta Infant Motor Scale (AIMS). It was observed that 58.82% of children had a normal motor development, 29.42% suspect motor development and 11.76% remaining have delayed motor development. The results indicate that the length of stay of children in day care centers are not leveraging the appropriate motor development of children, as it is not perceived improvement in motor behavior of children aged 12-18 months, when compared to children attending the nurseries for a shorter time (06-12 months old). In general it can be concluded that the process of motor development is influenced by environmental factors such as lack of good opportunities stimulus via appropriate toys, wider spaces to play and explore the environment among others, limiting motor performance of children in day care centers.